Labour market flexibility and unemployment duration: Evidence from the UK - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Using a combination of UKHLS and LFS data and a discrete time model, we test the hypothesis that unstable jobs with variable hours or pay enhance the job finding chances of the unemployed in the UK. We nd no evidence that the share of unstable jobs in the unemployed person's local labour market impacts on the probability to move into employment. This result holds both for men and women and for groups with low employability such as the low educated and the long-term unemployed. It is robust to alternative ways of de ning unstable jobs and to the inclusion of unobserved heterogeneity. Overall, ndings cast doubt on the importance of labour market exibility for employment creation.
Keywords: I31; J64; J81; J88; 330; labour market exibility; economic insecurity; unemployment duration; discrete time models